MATHEMATICAL MODELING OF CHEMICAL-TECHNOLOGICAL PROCESSES, INFORMATION PROCESSING - Turayev Kahramon Nortojiyevich (Web of Journals Publishing, 2025)
The article provides scientific and theoretical information on mathematical modeling of chemical-technological processes, data processing.
Keywords: Technological, mathematical, method, expression.